Strategi Manajemen Kepala Madrasah dalam Meningkatkan Mutu Pembelajaran Berbasis Nilai-Nilai Islam di Madrasah Ibtidaiyah - Hamdanah, Hamdanah (Auladuna: Jurnal Prodi Pendidikan Guru Madrasah Ibtidaiyah, 2024)
Abstract. This study aims to analyze the management strategies of Madrasah Ibtidaiyah principals in improving the quality of Islamic values-based learning. The research focuses on planning and organizing learning strategies, leadership implementation in execution and supervision, and identification of supporting and inhibiting factors. This research employs a qualitative approach with a case study method conducted at 2-3 high-performing Madrasah Ibtidaiyah. Data collection was carried out through in-depth interviews, participatory observation, documentation, and focus group discussions with research subjects including madrasah principals, teachers, madrasah committees, and supervisors. Data analysis uses the Miles, Huberman, and Saldana model with stages of data condensation, data display, and conclusion drawing. The findings reveal that madrasah principals implement integrative planning strategies based on the principle of consultation (shura) and organization based on trustworthiness (amanah). Instructional leadership is demonstrated through exemplary modeling (uswatun hasanah) and clinical supervision based on tarbiyah that focuses on continuous professional development. The main supporting factors are principal commitment, teacher dedication, and stakeholder participation, while inhibiting factors include budget constraints, gaps in teacher qualifications, and resistance to change. This study concludes that the integration of modern management functions with Islamic leadership values effectively improves holistic learning quality, encompassing both academic aspects and Islamic character formation. The practical implications of this research provide strategic guidance for madrasah principals and policy recommendations for the Ministry of Religious Affairs in madrasah leadership development.